Lack of Association of Intraventricular Hemorrhage with Retinopathy of Prematurity - Hand, Ivan; Shrier, Eric (Journal of Pediatric Neurology, 2019)
Objective Retinopathy of prematurity (ROP) is the primary cause of visual impairment in premature infants. Our objective was to study the relationship between ROP and intraventricular hemorrhage (IVH) in the premature infant.Methods This study was a retrospective chart review of very low birthweight infants of 1,500 g or less admitted to Kings County Hospital Center's neonatal intensive care unit who were screened for ROP over a 6-year period.Results Of 335 infants screened for ROP, 85 infants were identified to have ROP. Of these, 50 (56%) infants had stage 1 ROP, 25 (29%) had stage 2 ROP, 7 (8%) had stage 3 ROP, and 3 (4%) had stage 4 ROP. The incidence of IVH in our population was 14%. Multiple logistic regression demonstrated a significant association between ROP and gestational age (p = 0.001). There was no significant association between ROP stage and IVH grade. There was also no significant association between birthweight, ethnicity, or 5-minute Apgar score.Conclusions Our data demonstrated no association between IVH and severity of ROP. There was a statistically significant association between ROP and gestational age. We speculate that these data may be a reflection of improvement in neonatal care, with a declining incidence of IVH as well as increased ROP screening efforts.
Keywords: intraventricular hemorrhage; retinopathy of prematurity; premature